The Effect of Using Literacy Integrated Method on The Students’ Reading Achievement in Narrative - Hasibuan, Selamat Husni (IJET (Indonesian Journal of English Teaching), 2018)
This research was to investigate the effect of using literacy integrated method on the students’ reading achievement in narrative text. Population of this research was the second year students of Junior High School in SMP NEGERI 13 Binjai Jl. Letjend Jamin Ginting in the academic year 2017/2018. Two classes were taken by total sampling which divided into two groups, the first group VIII-1 which consisted of 36 students was experimental group which was given treatment by literacy integrated method and second group VIII-2 which consisted of 36 students was control group which was given treatment by using grammar translation method. Each group was given a pre-test and post-test. After the data had been collected, these were analyzed by using t-test formula. Based on the result of this research, it was concluded that there was significant effect of using literacy integrated method on the students’ reading achievement in narrative text.